PENINGKATAN KREATIVITAS MELALUI PELATIHAN GAME EDUKATIF BERBASIS ANDROID DI SMK N 1 KAWUNGANTEN - Yusuf, Dede; Famuji, Tri Stiyo; Sumantri, Raden Bagus Bambang; Hakim, Walidy Rahman (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance the creativity of students at SMK Negeri 1 Kawunganten through training in the development of Android-based educational games. The background of this initiative is the need to empower students to become creators of digital technology, rather than merely users, amid the rapid growth of the gaming and mobile technology industries. The training was conducted using the QuickAppNinja platform, which enables participants to create quiz-based games without requiring programming skills. The methods used included lectures, demonstrations, hands-on practice, and participatory evaluation, with an approach tailored for beginners. The activity lasted four hours and covered the introduction to educational game concepts, game creation practice, and evaluation sessions. The results showed that after the training, the majority (71%) of participants experienced an increase in confidence in developing Android-based applications and could follow the training process effectively, producing simple game prototypes. This training enhanced students’ digital literacy, technical skills, and confidence in creating digital products. In conclusion, the Android-based educational game training proved effective in fostering student creativity and is a relevant strategy to strengthen competencies in the creative industry era.